Characterization of the Development of Foals in Natural Mating and Embryo Transfer - Hunka, Monica Miranda; Souza, Luzilene Araújo; Silva, Elizabeth Regina Rodrigues da; Manso, Helena Emília Cavalcanti da Costa Cordeiro; Filho, Hélio Cordeiro Manso (Acta Scientiae Veterinariae, 2017)
Background: Several reproductive biotechnologies are used in horses and embryo transfer (ET) is one of the most frequent in countries like Brazil and the USA. It has been shown that animals originated by new reproductive technology can have compromised growth in extreme conditions, however there are still only a few researches on the influence of embryo transfer over lactating foals under different raising methods. Due to the lack of studies on ET products development and the need to understand the process and it’s relate with lactating foal’s growth, the aim of this study was to evaluate the influence of the embryo transfer and natural mate over the newborn foals. Materials, Methods & Results: From a group of 20 mares, 20 Quarter Horse lactating foals were used (10 natural matting + 10 embryo transfer). The mares weren’t given any concentrate feed during whole gestation and lactation. Foals were kept with the mare, however was used creep feeding to give commercial feed ad libitum. The foals biometric evaluation were made at the day of birth (day 0) and at 30th, 60th, 90th, 120th and 150th day (weaning) for the following parameters: body mass (BM), height at the withers (H), heart girth (HG), cannon bone girth (CBG) and fat mass percentage (FMP). The fat thickness percentage at rump it was determined by ultrasound device. All statistics were considered significant when a P < 0.05 was detected. It wasn’t observed corporal mass differences between the groups of mares and the group of stallions. Milk’s components evaluation hasn’t showed differences for the assessed parameters on both mare groups. Evaluating lactating foals’ development, significant differences were observed for height (H), heart (HG) and cannon bone girth (CBG) and body mass (BM). Discussion: In this actual research, Natural Mating (NM) and Embryo Transfer mares exhibited similar corporal mass (P > 0.05) and so did foals at birth (P > 0.05). However, by the time of weaning, body mass (BM) was 25% higher on ET foals group. These results indicate some influence of ET on foals’ growth since milk’s composition on both groups (G-NM and G-ET) was similar (P > 0.05), as well as dietary and sanitary handling that foals and mares were submitted to. It is a fact that one’s phenotype is determined not only by its genotype, there is evidence that environmental modification during intra uterine period, as well as extra uterine environment may affect epigenetic features. Changes of physical and skeleton progress patterns on suckling foals remained after weaning. However it could be observed that the present study foals had their development under proposed parameters according to prior studies, which affirm that animals have to duplicate their birth weight at the first month of age and should be five times higher at weaning. It stands out that ET treatment foals reported slightly high values indicating this research and future studies relevance to assure if growth beyond observed commonly is beneficial or damaging. In conclusion, there is little influence of the reproductive method over the lactating foal’s development when we compered two groups of foals obtained from natural mate and embryo transfer. However, foals from embryo transfer had large body mass at weaning when compared with natural mate group. Finally, the mares’ milk composition was similar between both groups of mares used in this study.